Exploring the Determinants of Intrinsic Interest among Undergraduate Accounting Students - Sofik Handoyo (Intelektual Pustaka Media Utama, 2018)
The purpose of the study is to identify the determinants that are closely associated with intrinsic interest among undergraduate accounting students. Descriptive statistical analysis and correlation analysis were applied in this study. The data was generated through questionnaire instruments using the seven points of the Likert scale. The study involved 136 samples of undergraduate accounting student at Universitas Padjadjaran. Reliability and Validity tests were conducted to make sure the items of questions are valid and the internal consistency are present. There are five independent variables in this research, namely intrinsic interest, extrinsic interest, self-efficacy, parental and peer influence, and anticipated conflict. Results indicate that extrinsic interest and self-efficacy are positively and significantly associated with the intrinsic interest of undergraduate accounting student. Meanwhile, parental and peer influence and anticipated conflict are negatively associated with the intrinsic interest of undergraduate accounting students. The magnitude of correlation for anticipated conflict is significant, however, parental and peer influence was found not significant